An Analysis of Effects of Test Misconduct on Students’ Perception of Assessment Quality in Nigeria Federal Colleges of Education. - Dickson-Omogoye, Blessing; Adeleke , Joshua O. (African Journal of Behavioural and Scale Development Research, 2023)
Test misconduct is a prevalent issue in Nigeria's education system, particularly in colleges of education. This paper analysed the effects of test misconduct on students' perception of assessment quality in these institutions. The research employed a mixed-methods strategy to collect extensive data on the experiences and viewpoints of the students by combining the use of questionnaire, focus group discussion and in-depth interviews. The study found answers to two research questions and tested an hypothesis. The results show that most of the federal colleges of education in south west Nigeria have disciplinary committees that deal with test misconduct cases which may emanate from both staff and students. From the interviews and focus group discussion it is event that the severity of punishment mete to offenders signalled strong warning to the entire academic community to steer clear of illicit activities. Results from the study also show that 70 % of the students observed do not doubt the integrity of test administration procedures. Only a few have lesser confidence in the final output of Tests, as a result of observed greed and lackadaisity, of lecturers. The result also revealed a statistical significant relationship between students’ perception of quality of assessment and their perception of test misconduct which is significant at p<0.05 (r = 0.59; p = 0.00). In order to tackle this problem, it was recommended that comprehensive strategies such as fostering academic honesty, and offering sufficient assistance for students' education and preparation, be adopted. Promoting a culture characterised by integrity and a system based on individual merit can help to rebuild students' trust in the evaluation process. Keywords: Test, misconduct, Perception, Assessment, Quality